Hubungan Motivasi dan Dukungan Keluarga dengan keikutsertaan prenatal yoga pada ibu hamil: Array (LPPM STIKes Buleleng, 2020)
This study aims to analyze the relationship of motivation and family support with prenatal yoga. This study uses correlation analytic design with cross sectional approach. The sample in this study was pregnant women who met the inclusion criteria of 124 respondents. Data collection tool is a questionnaire. Bivariate analysis with Chi Square correlation test. Bivariate analysis between motivation and family support has a significant relationship with participation in prenatal yoga, all variables have a p value <0.001. Motivation and family support have a significant relationship with participation in prenatal yoga.